2018
DOI: 10.1080/10903127.2018.1501445
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Prehospital Chemical Sedation With Ketamine Versus Haloperidol and Benzodiazepine or Physical Restraint Only

Abstract: This study demonstrates a lower intubation rate in patients administered ketamine than prior literature in association with a lower weight-based dosing regimen. Ketamine use was correlated with a higher frequency of intubation and a greater need for additional chemical restraint when compared with other restraint modalities, though exogenous factors such as provider preference may have impacted this result. There was no difference in ED length of stay or admission rate between the ketamine and haloperidol plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…In a further retrospective study, it was found that patients who receive ketamine need intubation more frequently, and they also often need haloperidol and benzodiazepines in their further course (27). The two studies just mentioned were published too late to be included in the analysis for the current clinical practice guideline.…”
Section: Ketaminementioning
confidence: 99%
“…In a further retrospective study, it was found that patients who receive ketamine need intubation more frequently, and they also often need haloperidol and benzodiazepines in their further course (27). The two studies just mentioned were published too late to be included in the analysis for the current clinical practice guideline.…”
Section: Ketaminementioning
confidence: 99%
“…5 Prior studies have compared the use of intramuscular (IM) ketamine to traditional IM haloperidol and IM benzodiazepines for control of acute agitation. 7,8 Time to sedation with ketamine was significantly faster than haloperidol (five minutes versus seventeen minutes). However, complication rates were significantly higher with ketamine administration than haloperidol alone.…”
Section: Introductionmentioning
confidence: 99%
“…7,9,10 Comparison of intubation rates between ketamine and haloperidol use in acute agitation revealed ketamine had a significantly higher intubation rate than haloperidol and a combination of haloperidol and benzodiazepines. 7,8 Patients who received ketamine were also more likely to require additional chemical sedation and restraint compared to patients who received haloperidol and benzodiazepines. 8 There is some equipoise in the literature regarding whether there is a direct relationship between ketamine dose and subsequent intubation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations